2003
DOI: 10.1016/s0022-3093(02)01815-x
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer and optical spectroscopic study of temperature and redox effects on iron local environments in a Fe-doped (0.5 mol% Fe2O3) 18Na2O–72SiO2 glass

Abstract: Mossbauer and optical spectroscopic study of temperature and Mossbauer and optical spectroscopic study of temperature and redox effects on iron local environments in a Fe-doped (0.5 mol% redox effects on iron local environments in a Fe-doped (0.5 mol% M€ o ossbauer and optical spectroscopic study of temperature and redox effects on iron local environments in a Fe-doped (0.5 mol% Fe 2 O 3) 18Na 2 O-72SiO 2 glass

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…A significant distortion of the polyhedra also indicates this, while the oxygen polyhedra of the network forming ions usually have higher degree of symmetry. The obtained results are in agreement with the results in the litera ture from studies on the structural state of iron in glass using various spectroscopic methods [20,[30][31][32][33][34][35][36][37], including the Mössbauer spectroscopy method in glass for the immobilization of radioactive waste [38][39][40].…”
Section: Discussionsupporting
confidence: 88%
“…A significant distortion of the polyhedra also indicates this, while the oxygen polyhedra of the network forming ions usually have higher degree of symmetry. The obtained results are in agreement with the results in the litera ture from studies on the structural state of iron in glass using various spectroscopic methods [20,[30][31][32][33][34][35][36][37], including the Mössbauer spectroscopy method in glass for the immobilization of radioactive waste [38][39][40].…”
Section: Discussionsupporting
confidence: 88%
“…Lubas et al [11] studied by IR some glasses prepared mainly from basalt and found that these samples have high crystallization capability when heat treated. Many other articles have been published concerned with the study of various glasses with composition similar to that of the present samples [12][13][14].…”
Section: Introductionmentioning
confidence: 90%
“…[63][64][65][66] These observations suggest that both the loading of Gd 2 Ti 2 O 7 in the composite and the annealing temperature affect the silicate network in the glass-ceramic composite materials. when the composites were annealed at 750 o C, which can be described by the following equilibrium reaction: 4Fe 3+ +2O 2- [70][71][72][73] The reduction of Fe 3+ to Fe 2+ at 1100 o C may also be caused by Gd 2 Ti 2 O 7 crystallites dissolving in the glass matrix when the composite materials were annealed at this temperature. These observations indicate that the oxidation state and CN of Fe in the composite materials are strongly affected by the annealing temperature.…”
Section: Si L 23 -Edge Xanesmentioning
confidence: 99%